2022
DOI: 10.3390/s22083066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Feature Selection Methods for Classification of Epileptic Seizure EEG Signals

Abstract: Epilepsy is a disease that decreases the quality of life of patients; it is also among the most common neurological diseases. Several studies have approached the classification and prediction of seizures by using electroencephalographic data and machine learning techniques. A large diversity of features has been extracted from electroencephalograms to perform classification tasks; therefore, it is important to use feature selection methods to select those that leverage pattern recognition. In this study, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
0
14
1
Order By: Relevance
“…The comparison showed that SAW had better accuracy and . Regarding , it exceeded the study by Sánchez et al [ 55 ], but as SAW tends to preserve a Negative-class majority, it had a lower than Dissanayake et al [ 44 ].…”
Section: Implementation and Resultscontrasting
confidence: 67%
“…The comparison showed that SAW had better accuracy and . Regarding , it exceeded the study by Sánchez et al [ 55 ], but as SAW tends to preserve a Negative-class majority, it had a lower than Dissanayake et al [ 44 ].…”
Section: Implementation and Resultscontrasting
confidence: 67%
“…For each of the 3 filtered ear EEG signals, the following statistical variables were calculated in each of the windows [ 40 , 41 , 42 ]: mean, median, mode, standard deviation, variance, absolute deviation, 25th percentile, 75th percentile, interquartile range, kurtosis, skewness and harmonic mean. In addition, spectral power [ 43 ] and entropy were also calculated, thus generating the following characteristics: mean spectral power, maximum spectral power value, maximum frequency of the maximum spectral power value, median entropy, maximum entropy value and minimum entropy value.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical properties, such as mean, median, variance, standard deviation, skewness, kurtosis, peak amplitude, minimum amplitude, peak to peak, and similar, are the simplest features that may be derived from an EEG signal in the time domain [ 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Hjorth parameters are based on the variance of the subsequent derivatives of the EEG signal.…”
Section: Discussionmentioning
confidence: 99%